Gender, Ethnicity and the Politics of Belonging in Postcolonial Africa/Cameroon: A Reading of Lola Perpetua Nkamanyang’s The Lock On My Lips - Niba, Nforbin Gerald (Advances in Social Sciences Research Journal, 2023)
Gender and Ethnicity are two key types of group distinctions with which group-based power is associated and, in a multi-cultural Postcolonial context like Cameroon, gender and ethnicity intersect to shape our identities, opportunities and the challenges we face in life. Lola Pepertua Nkamanyang’s The Lock on My Lips falls within the corpus of literature on group-based power and discrimination, leading to a hardening of identities around claims to belong and an opposite process of excluding outsiders. Drawing from minority theories, gender and postcolonial theories, this study investigates the intersection of gender, ethnicity and power in the play. The paper argues that the ethnic tension replicates the Anglophone/francophone divide in a bi-cultural Cameroon. Seen thus, Lola follows in the footsteps minority writers like Victor Epie Ngome to weave her drama around a marital conflict between two people from different ethnic backgrounds whose union is characterized by marginalization, assimilation and dictatorship. However, Lola treats this sensitive subject in a rather kaleidoscopic, suggestive and pacifist way, recognizing like her radical predecessor that the reunified nation has been rendered fragile and diseased by the marginalization of women and the Anglophone minority, Lola rather opts for healing. A unionist, Lola believes that nation-building can be effective, if it is founded on mutual respect and equal opportunities for the sexes and for the two ethnic/linguistic groups of Cameroon. The significance of the marriage metaphor in her play lies in her espousal of gender equality, cultural syncretism and peaceful co-existence of husband and wife, and of Anglophones/Francophones.